OPTIMALISASI BACA TULIS Al-QUR’AN PESERTA DIDIK SEKOLAH DASAR NEGERI 73 PAREPARE - Syukri Syukri (IAI DDI Mangkoso, 2024)
to read and write the Koran among students at SDN 73 Parepare. As a complement, the type of research used is field research with a qualitative approach with research instruments and data collection procedures that are guidelines for observation, interviews and further documentation, data processing and analysis techniques, namely; data reduction, data presentation, drawing conclusions, and data interpretation. Check the validity of the data, namely; credibility of the informant, time of disclosure, conditions experienced. The results of the research show that students at SDN 73 Parepare still experience difficulties in reading and writing the Al-Qur'an because students are not yet accustomed to reading Arabic letters or hijaiyyah, let alone the law on reading the Al-Qur'an. or recitation. The existing phenomenon is a system of teaching the Koran which is limited to reading only. Optimizing reading and writing the Koran for students at SD Negeri 73 Parepare, namely by knowing the level of ability of each student by understanding student characteristics, choosing the right methods and strategies for learning to read and writing the Koran, creating a comfortable learning place , building relationships with students, conducting evaluations, and providing motivation to students